A case of PURA syndrome in a newborn child (neurodevelopmental disorder syndrome with neonatal respiratory failure, hypotension and feeding difficulties; nEDRIHf(OMIM 616158)) - L. V. Kravchenko; K. I. Lazareva; L. I. Monat; M. A. Levkovich (Медицинский вестник Юга России, 2023)
A clinical observation of a newborn child with an extremely rare disease - PURA syndrome is presented. In the world scientific literature, there is a limited number of publications devoted to this pathology, which is the main reason that determines the complexity of diagnosis. This case demonstrates the need for persistent severe myasthenic syndrome in newborns, in addition to excluding hereditary metabolic diseases, to conduct whole genome DNA sequencing to detect PURA syndrome. A clinical case in a young child is presented as an example of a severe illness with an unfavorable course and the likelihood of a worsening separated prognosis.   The goal was to highlight the clinical manifestations, the complexity of the treatment of this pathology by neonatologists, pediatricians, neurologists from the standpoint of improving the quality of diagnosis of this pathology.